2017
DOI: 10.1186/s40781-017-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of ghrelin in the pancreatic exocrine secretion via mitogen-activated protein kinase signaling in rats

Abstract: BackgroundThis study was performed to investigate the impact of exogenous ghrelin on the pancreatic α-amylase outputs and responses of pancreatic proteins to ghrelin that may relate to pancreatic exocrine.MethodsSprague-Dawley male rats (9 weeks old, 300 ± 10 g) were injected with ghrelin via intraperitoneal (i.p.) infusion at dosage of 0, 0.1, 1.0 and 10.0 μg/kg body weight (BW), respectively. The plasma ghrelin and cholecystokinin (CCK) level were determined using enzyme immunoassay kit; the mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Ghrelin is a polypeptide comprising 28 amino acids that can regulate animal food intake through central regulation or peripheral stimulation (Song et al 2019;Abtahi et al 2017). Studies have demonstrated that central or peripheral injections of Ghrelin can stimulate mammalian food intake and weight gain (Hyland et al 2020;Lee et al 2017;Okuhara et al 2018). However, in poultry, Ghrelin's role is not consistent with the results in mammals (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is a polypeptide comprising 28 amino acids that can regulate animal food intake through central regulation or peripheral stimulation (Song et al 2019;Abtahi et al 2017). Studies have demonstrated that central or peripheral injections of Ghrelin can stimulate mammalian food intake and weight gain (Hyland et al 2020;Lee et al 2017;Okuhara et al 2018). However, in poultry, Ghrelin's role is not consistent with the results in mammals (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%